When is cultural input central? The development of ontological beliefs about religious and scientific unobservables. (16th November 2021) - Davoodi, Telli; Clegg, Jennifer M.
Abstract: Across diverse cultural contexts, children and adults believe in the existence of religious and supernatural unobservables (e.g., gods, angels) as well as scientific and natural unobservables (e.g., germs, oxygen). In this article, we explore the role of cultural input and testimony in children's developing beliefs in supernatural and natural unobservables as real. We review cross‐cultural research with children and adults on their beliefs about the ontological status of religious and scientific unobservables and the epistemic patterns associated with these beliefs. Based on this evidence, we argue that cultural input plays a central role in the development of belief about supernatural unobservables as real, whereas it plays a less critical role in the development of belief about natural unobservables as real. In the latter case, we argue that direct experiences with the natural world combine with children's naive theories to generate beliefs about natural unobservable entities and processes as real.